Sjogren's syndrome: apoptosis by anti-SSA and anti-SSB antibodies - A. Scagliusi; S. D'Amore; M. D'Amore; P. Scagliusi (PAGEPress Publications, 2011)
The pathogenesis of the Sjogren's Syndrome (SjS) has not yet been completely defined. However, the cell-mediated immunity plays an important role and the apoptosis of the ductal and acinar epithelial cells is responsible of the glandular tissue damage, through the cytotoxic T-cells, particularly of the CD4+ subpopulation, by the release of proteases (such as perforin and granzyme B) and by the interaction of the Fas Ligand (FasL; CD95L) of the T-lymphocytes, with the Fas (Apo-1; CD95) of the epithelial cells. The apoptotic death of the epithelial cells is the autocrine Fas/FasL interaction also. The anti-SSA and anti-SSB antibodies are the immunological markers of the Sjogren's syndrome, but it is not yet understood if they have pathogenetic implications....